2020
DOI: 10.1136/bmjopen-2020-039824
|View full text |Cite
|
Sign up to set email alerts
|

Impact of secondhand smoke exposure on cognitive function among middle-aged and older women in China: findings from three waves of the China Health and Retirement Longitudinal Study

Abstract: ObjectivesTo examine the association between secondhand smoke (SSH) and women’s global cognitive function and cognitive subdomains.DesignCohort study.ParticipantsData for this study were obtained from the China Health and Retirement Longitudinal Study (2011-2013-2015), and pooled analysis was applied to wave 1 and wave 2 (2011–2013), wave 2 and wave 3 (2013–2015) and wave 1 and wave 3 (2011–2015). Data from a total of 6875 Chinese women with normal cognitive function at baseline were selected for analysis, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Controversy exists on the association between SHS and cognitive functioning in older adults, although a limited number of studies have examined the relationship between the two and found a negative cognitive effect of SHS. In a longitudinal study of 6875 middle-aged and older Chinese women, women who had lived with a smoking husband experienced a signi cantly faster decline in global cognitive function, visuospatial ability, and episodic memory function than those who had not (Bai et al, 2020). However, in that study, researchers failed to adjust important covariates such as body mass index, exercise, and alcohol use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversy exists on the association between SHS and cognitive functioning in older adults, although a limited number of studies have examined the relationship between the two and found a negative cognitive effect of SHS. In a longitudinal study of 6875 middle-aged and older Chinese women, women who had lived with a smoking husband experienced a signi cantly faster decline in global cognitive function, visuospatial ability, and episodic memory function than those who had not (Bai et al, 2020). However, in that study, researchers failed to adjust important covariates such as body mass index, exercise, and alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have examined the effect of SHS on cognitive functioning in this population (Llewellyn et al, 2009). Among the existing studies, many used participants' self-report exposure to SHS (Bai, Jin, & Huang, 2020;Barnes et al, 2010;Friedrich, 2007;Heffernan & O'Neill, 2013) and thus was unprecise and subject to recall and report bias. Thus, studies involving the use of biomarkers to objectively measure the extent of SHS are needed to clarify its relationship with cognitive functioning in this growing population.…”
Section: Introductionmentioning
confidence: 99%
“…65 Even secondhand smoke, particularly over a long duration, has been associated with worse cognitive function. 66…”
Section: Smokingmentioning
confidence: 99%
“…In children, SHS can lead to the development of ear infections, asthma, and respiratory infections including fatal sudden infant death syndrome; in adults, it is linked to an increased risk of cardiovascular diseases and lung cancers [2]. Household SHS exposure was associated with a significant decline in global cognitive function, visuospatial ability, and memory function among Chinese women [14].…”
Section: Introductionmentioning
confidence: 99%